Imaging Mass Cytometry and Single-Cell Genomics Reveal Differential Depletion and Repletion of B-Cell Populations Following Ofatumumab Treatment in Cynomolgus Monkeys - Theil, Diethilde; Smith, Paul; Huck, Catherine; Gilbart, Yoann; Kakarieka, Algirdas; Leppert, David; Rauld, Celine; Schmid, Cindy; Baumgartner, Reto; Stuber, Nathalie; Cordoba, Francisco; Dubost, Valerie; et al. (Frontiers in Immunology, 2019)
Ofatumumab is the first, fully human, anti-CD20 monoclonal antibody in Phase 3 development for multiple sclerosis (MS). The study focused on changes in lymphocyte subsets in blood and lymphoid tissues and on potential novel biomarkers as a result of anti-CD20 antibody action in Cynomolgus monkeys treated with human equivalent doses of subcutaneous (s.c.) ofatumumab on Days 0, 7, and 14. Axillary lymph nodes (LNs) and blood samples were collected at various time points until Day 90. Lymphocyte subsets were quantified by flow cytometry, while morphological and immune cell changes were assessed by imaging mass cytometry (IMC), immunohistochemistry (IHC), and transcriptome analyses using single-cell methodology. Ofatumumab treatment resulted in a potent and rapid reduction of B cells along with a simultaneous drop in CD20+ T cell counts. The absolute numbers of marginal zone B cells in axillary LNs increased with treatment based on FACS analysis time. At Day 21, IHC revealed B-cell depletion in the perifollicular and interfollicular area of axillary LNs, while only the core of the germinal center was depleted of CD20+CD21+ cells. By Day 62, the perifollicular and interfollicular areas were abundantly infiltrated by CD21+ B cells and this distribution returned to the baseline cytoarchitecture by Day 90. By IMC CD20+CD3+CD8+ cells could be identified at the margin of the follicles, with a similar pattern of distribution at Day 21 and 90. Single-cell transcriptomics analysis showed that ofatumumab induced reversible changes in t-distributed stochastic neighbor embedding (t-SNE) defined B-cell subsets that may serve as biomarkers for drug action. In summary, low dose s.c. ofatumumab potently depletes both B cells and CD20+ T cells but apparently spares marginal zone (MZ) B cells in the spleen and LN. These findings add to our molecular and tissue-architectural understanding of ofatumumab treatment effects on B-cell subsets.